1996
DOI: 10.1002/(sici)1096-9861(19960715)371:1<104::aid-cne6>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for growth of supraspinal axons through the lesion after transection of the thoracic spinal cord in the developing opossum Didelphis virginiana

Abstract: In the present study, we asked whether supraspinal axons grow through a complete transection of the spinal cord in the developing opossum Didelphis virginiana. When the thoracic cord was transected at postnatal day (PD) 5 and bilateral injections of Fast Blue (FB) were made four segments caudal to the lesion 30-40 days later, FB-containing neurons were found in each of the supraspinal nuclei labeled by comparable injections in age-matched unlesioned controls. Continuity between the cut ends of the cord was obv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…We also have confirmed that in Monodelphis outgrowth fails after a critical period of approximately 12 days (Varga et al, 1995). The exact time window, or critical period, after which regeneration ceases to occur and nerve fibers fail to grow into a lesion depends on the species and on the maturity of the severed tract (see, e.g., McLaren and Taylor, 1995;Terman et al, 1996;Wang et al, 1996). One can presume that, as for dorsal root ganglion axons (Varga et al, 1995b), true regeneration of cut fibers accounts for a fraction of the growth and that new growth of uncut axons through the lesion may also contribute.…”
Section: Regenerationsupporting
confidence: 69%
“…We also have confirmed that in Monodelphis outgrowth fails after a critical period of approximately 12 days (Varga et al, 1995). The exact time window, or critical period, after which regeneration ceases to occur and nerve fibers fail to grow into a lesion depends on the species and on the maturity of the severed tract (see, e.g., McLaren and Taylor, 1995;Terman et al, 1996;Wang et al, 1996). One can presume that, as for dorsal root ganglion axons (Varga et al, 1995b), true regeneration of cut fibers accounts for a fraction of the growth and that new growth of uncut axons through the lesion may also contribute.…”
Section: Regenerationsupporting
confidence: 69%
“…Scale bar ϭ 100 µm in E. ventral horn, where they overlap with dorsally directed motoneurons (Qin et al, 1993); this is confirmed in the present study (note that Qin et al designate the day of birth as P1, making P4 equivalent to P3). In the opossum species Didelphis virginiana, ventral horn afferents could also be seen within the grey matter of the lumbar region, in close association with motoneuron dendrites, on the day of birth (Wang et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their immaturity at birth, the young are not only able to breathe and suck but they also make their way to the teat, although it is not clear whether this process involves a degree of help from the mother (Saunders et al, 1998). The use of Monodelphis domestica for developmental studies has been exploited in recent studies of spinal cord regeneration after traumatic injury (Nicholls and Saunders, 1996;Varga et al, 1996;Wang et al, 1997;Saunders et al, 1998). It has been shown that after complete transection of the thoracic spinal cord by crushing, there is a substantial degree of normal structural development in the crushed region and near-normal motor behaviour when the animals have grown to adulthood (Saunders et al, 1998).…”
mentioning
confidence: 99%
“…For example, functional regeneration is observed after spinal cord transection in opossums and rats during early gestational development (Wang et al, 1996; Fry et al, 2003; Lane et al, 2007). In addition, long distance axon regeneration within the spinal cord is observed after a crush injury of the adult rat filum terminale (Kwiecien and Avram, 2008).…”
mentioning
confidence: 99%